Triangulation of Salient Studies to Date on Trust‐Building in Mediation. Issue 3 (21st June 2020) - Riera Adrover, Joan Albert; Cuartero Castañer, María Elena; Campos Vidal, José Francisco
Abstract : Many studies have empirically demonstrated the importance of trust‐building between mediators and parties to a dispute. We wrote this article in response to a call by Stephen Goldberg and Margaret Shaw for studies conducted in North America to be triangulated in other countries where mediation is taking off as an alternative tool in the resolution of disputes. Our objective was to test theories on the factors that increase trust‐building in mediation. With this in mind, the study conducted by Jean Poitras in Montreal (Canada) was triangulated in the Balearic Islands (Spain) and an analysis was made of the similarities and differences between both studies using different methods.